Spontaneously Ruptured Dermoid Cysts and Their Potential Complications: A Review of the Literature with a Case Report - Rebecca Yuan Li; Yogesh Nikam; Supuni Kapurubandara (Case Reports in Obstetrics and Gynecology)
Spontaneous ruptures of dermoid cysts are a rare occurrence due to their thick capsules. This is the first systematic review on spontaneously ruptured dermoid cysts. A comprehensive literature search was performed from PubMed, Google Scholar, and MEDLINE. The cases were analysed for patient demographics, presenting signs and symptoms, imaging modalities used, management methods, and outcomes. The majority of cases report an idiopathic cause with symptoms of abdominal pain, distension, and fever. Computed tomography is the most accurate in detecting ruptured dermoid cysts. We also report a case of a 66-year-old who presented with sudden abdominal pain and a low-grade temperature. Imaging showed a 10 cm well-circumscribed hyperechoic mass consistent with a dermoid cyst with no suggestive signs of rupture. She was planned for a laparoscopic bilateral salpingo-oophorectomy. However, intraoperatively, a ruptured dermoid cyst was found with bowel adhesions and chemical peritonitis as cyst contents covered the entirety of the intra-abdominal cavity. Her operative course was complicated by inadvertent iatrogenic small bowel injury, unsuccessful laparoscopy, needing conversion to laparotomy. Despite their benign nature, complications from ruptured dermoid cysts include peritonitis, bowel obstruction, and abscesses. Surgical management by both laparoscopy and laparotomy is successful, with laparotomies more likely to be performed. Complications have mostly no long-term sequelae.